Exploring factors influencing university students’ entrepreneurial intentions: The role of attitudes, beliefs, and environmental support - Qing Liu; Michael Yao-Ping Peng (PLoS ONE, 2025)
Entrepreneurship is an increasingly popular career choice among students, driven by the transformative impact of emerging technologies and evolving professional landscapes. This study focuses on how higher education shapes students’ professional identities and entrepreneurial intentions, particularly among business school students. Utilizing the Theory of Planned Behavior (TPB) as the foundational framework, the study examines the factors influencing entrepreneurial intentions, with a specific emphasis on the moderating role of departmental identification. The primary aim of this research is to explore how students’ identification with their academic departments influences the relationship between entrepreneurial attitude, self-efficacy, and environmental support with entrepreneurial intentions. The study hypothesizes that the stronger the departmental identification, the more significant these relationships become. A survey is conducted among students from several public universities in the eastern provinces of Mainland China, yielding 1,632 valid responses. The results confirm a positive correlation between entrepreneurial attitude, self-efficacy, and environmental support with entrepreneurial intentions. Furthermore, departmental identification moderates these relationships, amplifying the effects when students identify strongly with their academic departments. These findings emphasize the critical role of departmental identity in shaping entrepreneurial aspirations. They highlight the need for higher education institutions to leverage departmental identity as a strategic tool to guide students’ career trajectories. By fostering a supportive academic environment that strengthens departmental identity, institutions can better prepare their students for entrepreneurial success in a rapidly evolving professional world.